Assessment of Dental Caries Experience and Its Association with Oral Hygiene Practices among 6–12 Years Old School Children in Silchar, Assam - Suranjana Jonak Hazarika; Devdoot Kakoti; Tulip Chakravarty; Jyotismita Thakuria; Gopal Kumar Sah; Sloka Kanungo (Journal of Primary Care Dentistry and Oral Health)
Aim: The aim of this study was to determine the prevalence of dental caries and its association with oral hygiene practices among 6–12 years old school-going children in Silchar, Assam. Methodology: A cross-sectional study was conducted among 240, 6–12 years school-going children for 3 months in Silchar, Assam, India. Oral hygiene practices and other sociodemographic data were recorded on a structured pro forma. Clinical oral examination was performed by a single examiner. Type III clinical examination was carried out using plane mouth mirrors and explorer. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 26.0. Results: The mean age of the study population was 10.75 ± 1.257. Mean decayed, missing, and filled teeth (DMFT) was higher among participants taking cariogenic food (1.295 ± 1.487) than those who were not taking it (1.295 ± 0.801). Furthermore, participants living in rural areas had higher DMFT (0.775 ± 1.205) as compared to those living in urban (1.406 ± 1.350). Conclusion: A significant proportion of school-going children was affected by dental caries. The most important predisposing factor for the occurrence of dental diseases in children is poor oral hygiene. Regular dental visits along with routine oral health education regarding good oral hygiene practices are the need of the hour.